The acquisition of Italian /r-l/ contrast by L1-Chinese learners. - Qiang Feng; Busà, M. Grazia (Journal of Monolingual & Bilingual Speech (JMBS), 2022)
The acquisition of Italian /r-l/ contrast by L1-Chinese learners has hardly been empirically investigated. This study aims to fill this gap. Thirty Chinese learners with different learning experiences and ten native Italian controls took part in a perception and a production experiment; their productions were assessed by three native Italian-speaking raters. The results show that, in perception, Chinese learners have some difficulty differentiating between Italian /r-l/ contrast. In production, Chinese learners have more difficulty properly realizing Italian /r/ than /l/, and show the tendency to replace /r/ with /l/. Also, while Chinese learners' production of Italian /r-l/ contrast varies with their increased learning experience, their perceptual accuracy remains unchanged. This nonparallel development suggests a possible dissociation between the two speech modalities in L2 speech acquisition.